2020
DOI: 10.1038/s41372-020-0724-z
|View full text |Cite
|
Sign up to set email alerts
|

Early assessment of lung aeration using an ultrasound score as a biomarker of developing bronchopulmonary dysplasia: a prospective observational study

Abstract: The objective of this study was to assess the predictive value of a lung ultrasound (LUS) score in the development of moderate-severe bronchopulmonary dysplasia (sBPD). This was a prospective observational diagnostic accuracy study in a third-level neonatal intensive care unit. Preterm infants with a gestational age below 32 weeks were included. A LUS score (range 0-24 points) was calculated by assessing aeration semiquantitatively (0-3 points) in eight lung zones on the 7th day of life (DOL) and repeated on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 41 publications
3
40
0
Order By: Relevance
“…In fact, in our study, VPI evolving to BPD with clinically significant hs-PDA were likely to be treated, but when adjusting for confounders, a treated hs-PDA was no longer significant. Oulego-Erroz et al [17] also found an excellent AUC for the LUS score to predict moderate-severe BPD with a cutoff point ≥8. The good performance of their score may be due to a higher correlation with days of MV because it assessed more posterior fields and included few patients with mild BPD.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In fact, in our study, VPI evolving to BPD with clinically significant hs-PDA were likely to be treated, but when adjusting for confounders, a treated hs-PDA was no longer significant. Oulego-Erroz et al [17] also found an excellent AUC for the LUS score to predict moderate-severe BPD with a cutoff point ≥8. The good performance of their score may be due to a higher correlation with days of MV because it assessed more posterior fields and included few patients with mild BPD.…”
Section: Discussionmentioning
confidence: 89%
“…It can assess dynamic changes over time and often detect them earlier than CXR. Recently, LUS has proven to be useful for respiratory management in VPI [16] and seems to be a promising tool for BPD [17][18][19]. In this study, we aim to compare LUS findings according to the diagnosis of BPD in VPI and to identify early clinical and echographic markers of BPD development in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Lung ultrasound (LU) is proving to be very useful in Neonatal Intensive Care Units (NICU): it diagnoses respiratory diseases with a higher accuracy than X‐ray, 1‐3 it predicts the need for admission for neonatal patients 4 and noninvasive ventilation failure, 5,6 and even the need for surfactant in preterm 7 and very low birth weight infants 8 . It also predicts bronchopulmonary dysplasia (BPD) in very low birth weight infants in the first week of life 9‐11 . Therefore, it is a harmless and easy‐to‐learn technique with high intraobserver and interobserver agreement 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The results of lung ultrasound have high diagnostic value in predicting the risk of developing BPD, but only after 1 week of life [ 27 ]. Despite the diagnostic value of echocardiography and lung ultrasound, the interpretation of the results of both these examinations is subjective, requires involvement of skilled specialists, and the examination itself requires additional costs.…”
Section: Discussionmentioning
confidence: 99%